Untouched: understanding the role of touch in obsessive-compulsive disorder - Flavian, Guy; Anholt, Gideon Emanuel; Peled-Avron, Leehe (Frontiers in Psychiatry, 2025)
People with Obsessive-Compulsive Disorder (OCD) engage in a wide array of rituals, including both visible behaviors and mental activities, with some of them involving the sense of touch. However, despite the essential role of touch in physical, emotional, and social interactions, the link between touch and OCD has not been thoroughly examined. This review explores the complex and under-investigated relationship between touch and OCD across three domains: (1) sensory phenomena, including “just-right” sensations and tactile over-responsivity; (2) social and interpersonal touch, particularly in the context of avoidance, reassurance-seeking, and comorbidities such as autism spectrum traits; and (3) therapeutic applications, including tactile exposures, mindfulness-based interventions, and somatic practices. We distinguish between discriminatory and affective touch and examine how disruptions in these systems may contribute to symptom expression and maintenance. While empirical research in this area remains limited, we propose a conceptual framework to guide future studies, emphasizing clinical implications for assessment and treatment. Cultural and ethical considerations are also discussed, particularly regarding the use of touch in therapy for individuals with contamination-based OCD.